Tanggung Jawab Direksi Terhadap Perbuatan Melawan Hukum Atas Akta Perjanjian Kredit - Nirwana Resti; Ahmad Fauzi; Masitah Pohan (Mahesa Research Center, 2021)
While the loan-receivable agreement is generally used by the public and is not related to the bank.This type of research is normative legal research. What is meant by juridical normative research is research used to study the application of legal norms or norms. Regulations Regarding Responsibility for Acts Against the Law on Credit Agreement Deeds, which are carried out by the board of directors are regulated in Article 1365 of the Civil Code regarding Acts Against the Law, the Code of Commercial Law, namely PT Regulations in the KUHD described in articles 36 to 56. The further discussion regarding PT as a legal entity is regulated in Law Number 40 of 2007, Article 1 point 2, namely the general meeting of shareholders, directors and commissioners who have their respective functions and duties as well as authority. And Article 52 of Law Number 30 of 2004 concerning the Position of Notary Public.